Memberdayakan Siswa SMA Di Kecamatan Alas, Sumbawa: Strategi Bimbingan Karir untuk Menghadapi Tantangan Masa Depan - Gunawan, Gunawan; Kosim, Kosim; Zuhdi, Muhammad; Taufik, Muhammad; Rahayu, Satutik (Indonesian Journal of Education and Community Services, 2024)
Education in Alas Subdistrict, Sumbawa, faces challenges in preparing high school students for the future. Students often lack adequate information and guidance regarding career choices and higher education opportunities. This community service activity aimed to empower high school students in the Alas Subdistrict through a comprehensive career guidance strategy. The methods included counseling, information discussions, and question-and-answer sessions regarding study opportunities, study program choices, learning tips, and available scholarships. Students showed high enthusiasm, as seen from the many questions and their active participation in discussions. As a result, students better-understood career opportunities, including various study programs and university entrance pathways, and increased motivation to pursue higher education. This activity provides recommendations for schools and stakeholders to improve career guidance programs and better prepare Alas Subdistrict high school students for future challenges.